A Review on Load Balancing Algorithms in Cloud Computing Environment - Yadav, Mala; Prasad, Jay Shankar (International Journal of Computer Sciences and Engineering, 2025)
Virtualized Cloud Computing environment having the ability to change the IT software industry. Various practices and technologies are influenced by this amazing platform of next stage of evolution of internet. Information technology industry modernized by facilitating flexible on-demand allocating of computing resources. These issues are driving forces for the formation of an effective load balancing algorithm. Load serves in various forms as network load, CPU load and memory. Load balancing mechanism improved resource utilization, job response time and minimize migration by distributing the load among various nodes in a distributed system. To achieve effective load balancing the situation like some of the nodes are heavily loaded and some are under-loaded must be avoided. Load balancing algorithm must ensure that every node in the network distributes equal amount of work to all the processors. Load Balancing plays a critical role in cloud computing environment. Efficient load balancing algorithm provides customer’s on-demand basis in pay-as-you-use-manner resource. This paper presents several load balancing algorithms in diverse cloud computing environment